Loneliness in College Students - Izzatul Fithriyah (Jurnal Psikiatri Surabaya, 2024)
Introduction: Loneliness among college students is quite prevalent. Students in their early years experience a transition period when entering university. Conditions with a new living environment, a new social environment, adjustments to peer relations, and a new academic atmosphere, support the occurrence of loneliness conditions in students. This study aims to understand loneliness in college student Methods: Literature ReviewResults: College students have a greater risk of experiencing loneliness. The impact of loneliness on students is also quite significant, both physically and psychologically. Loneliness can affect mental conditions of depression, anxiety, suicide, and low self-esteem which will ultimately lead to a decrease in quality of life. The physical effects of loneliness can also result in prolonged feelings of fatigue, limited physical activity, cardiovascular disorders, and unhealthy lifestyles which ultimately also have an impact on decreasing quality of life. Intervention and prevention to overcome loneliness are urgently needed, such as improving social skills, overcoming and adapting maladaptive social cognition, increasing social support, mindfulness interventions, and improving friendships. Conclusions: Prevention programs for loneliness are very important to implement. Such an intervention could help reduce the burden of the disease in students’ future professional lives. Keywords: Loneliness, Well-Being, College Students